PHARMACISTS KNOWLEDGE, PERCEPTION, AND READINESS FOR TELEPHARMACY IMPLEMENTATION: A SYSTEMATIC REVIEW - Eko Yatminto; Nanang Munif Yasin; Chairun Wiedyaningsih (Journal Pharmaceutical Science and Application, 2024)
Background: Telepharmacy has emerged as the latest approach for remote pharmaceutical services. However, some factors influence the success of this technology, such as pharmacists knowledge, readiness to adopt, and perspectives. Objective: This study aims to evaluate the level of knowledge, perception, and readiness to use telepharmacy systems among pharmacists. Methods: Articles from PubMed, Google Scholar, and Scopus (November 2023) were reviewed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines in 2022. Inclusion criteria encompassed cross-sectional studies examining knowledge, perception, and readiness to use telepharmacy among pharmacists within the last ten years. The quality of studies was assessed using the Joanna Briggs Institute Critical Appraisal Checklist. Results: Eight articles were included in the study, with the largest respondent pool from a study in Vietnam (414) and the smallest from Indonesia (78). All included articles demonstrated good quality with no significant bias. Five studies discussed knowledge levels, with four showing good knowledge (89.74%, 82.67%, 62.3%, 96.83%). Regarding telepharmacy perspectives, two studies had less favorable perspectives. Three studies indicated adequate readiness for telepharmacy implementation (87%, 72%, 63.23%), while one was unprepared (27.74%). Conclusion: Most studies show good knowledge, perception, and readiness to implement telepharmacy. There is a need for telepharmacy training programs in pharmacy schools or hospitals. Keywords: Telepharmacy; Knowledge; Perception; Readiness to Use; Pharmacists